Hidden in plain sight: antisemitic content in QAnon subreddits - Dana B. Weinberg; Meyer D. Levy; April Edwards; Jeffrey S. Kopstein; David Frey; Peter Antonaros; Nikola Baci; Noah D. Cohen; Javier A. Fernandez; Yunis Ni (PLoS ONE, 2025)
When is online content antisemitic? This matter is highly contested, except in the case of explicit language. Yet implicit antisemitic content and conspiracy narratives about Jews have been on the rise, especially on moderated platforms. This paper maps empirically the connections between explicit antisemitic content and these other forms of content, showing the language game at play in an online community identified as antisemitic and providing a relatively simple answer to the classification of content question. Using data from two QAnon subreddits, r/CBTS_Stream and r/greatawakening, we identify the co-occurrence of explicit and implicit antisemitic language posted to the subreddits. The language game involves an ingroup having specialized knowledge related to implicit language or dog whistles; the ingroup knows and uses the secret meaning of these terms as an insider’s code. Content network analysis and qualitative coding illustrate that QAnon taught this insider’s code by presenting the overt, antisemitic meanings of implicit terms and generalized narratives in posts that combined them with explicit language. While explicit language appeared rarely and was used by only a small proportion of users, more than a third of QAnon users employed implicit antisemitic language in their posts. This implicit language communicated antisemitic conspiracy narratives and antisemitic ideas more generally, to an audience “in the know” while also offering the user plausible deniability. Moreover, the implicit antisemitic terms circumvent platform censorship and provide an opportunity to leverage common ground around antisemitic conspiracy narratives with new users without the stigma of explicitly antisemitic content. The question of whether content is antisemitic may easily be answered by looking at a community’s posts that combine explicit and implicit antisemitic language. (272 words).